Odpowiedź :
A) {4a-2=b
{3a+7b=1,5
b=4a-2
3a+7(4a-2)=1,5
b=4a-2
3a+28a-14=1,5
b=4a-2
31a=1,5+14
b=4a-2
31a=15,5/31
b=4a-2
a=0,5
b=4*0,5-2
a=0,5
b=0
a=0,5
B) {5x=4-2y
{4x+y=3
5x=4-2y
y=3-4x
5x=4-2(3-4x)
y=3-4x
5x=4-6+6x
y=3-4x
5x-6x=-2
y=3-4x
-x=-2/*(-1)
y=3-4x
x=2
y=3-4*2
x=2
y=-2
C){6x-3y=9
{x+5y=-9.5
6x-3y=9
x=-9,5-5y
6(-9,5-5y)-3y=9
x=-9,5-5y
-57-30y-3y=9
x=-9,5-5y
-33y=9+57
x=-9,5-5y
-33y=66/:(-33)
x=-9,5-5y
y=-2
x=-9,5-5*(-2)
y=-2
x=-9,5+10
y=-2
x=0,5
{3a+7b=1,5
b=4a-2
3a+7(4a-2)=1,5
b=4a-2
3a+28a-14=1,5
b=4a-2
31a=1,5+14
b=4a-2
31a=15,5/31
b=4a-2
a=0,5
b=4*0,5-2
a=0,5
b=0
a=0,5
B) {5x=4-2y
{4x+y=3
5x=4-2y
y=3-4x
5x=4-2(3-4x)
y=3-4x
5x=4-6+6x
y=3-4x
5x-6x=-2
y=3-4x
-x=-2/*(-1)
y=3-4x
x=2
y=3-4*2
x=2
y=-2
C){6x-3y=9
{x+5y=-9.5
6x-3y=9
x=-9,5-5y
6(-9,5-5y)-3y=9
x=-9,5-5y
-57-30y-3y=9
x=-9,5-5y
-33y=9+57
x=-9,5-5y
-33y=66/:(-33)
x=-9,5-5y
y=-2
x=-9,5-5*(-2)
y=-2
x=-9,5+10
y=-2
x=0,5
a)
{4a-2=b
{3a+7b=1,5
{b=4a-2
{3a+7(4a-2)=1,5
3a+28a-14=1,5
31a-14=1,5/+14
31a=15,5//31
a=0,5
{a=0,5
{b=4*0,5-2
{a=0,5
{b=0
b)
{5x=4-2y
{4x+y=3
{x=[(4-2y)/5]
{4x+y=3
4[(4-2y)/5]+y=3
[(16-8y)/5]+y=3
3,2-1,6y+y=3
3,2-0,6y=3/*10
32-6y=30/-32
-6y=-2//(-6)
y=(1/3)
{y=(1/3)
{x={[4-(2/6)]/5}
{y=(1/3)
{x=(11/15)
c)
{6x-3y=9
{x+5y=-9,5
{6x-3y=9
{x=-9,5-5y
69-9,5-5y)-3y=9
-57-30y-3y=9
-57-33y=9/+57
-33y=66//(-33)
y=-2
{y=-2
{x=-9,5-5*-2
{y=-2
{x=0,5
{4a-2=b
{3a+7b=1,5
{b=4a-2
{3a+7(4a-2)=1,5
3a+28a-14=1,5
31a-14=1,5/+14
31a=15,5//31
a=0,5
{a=0,5
{b=4*0,5-2
{a=0,5
{b=0
b)
{5x=4-2y
{4x+y=3
{x=[(4-2y)/5]
{4x+y=3
4[(4-2y)/5]+y=3
[(16-8y)/5]+y=3
3,2-1,6y+y=3
3,2-0,6y=3/*10
32-6y=30/-32
-6y=-2//(-6)
y=(1/3)
{y=(1/3)
{x={[4-(2/6)]/5}
{y=(1/3)
{x=(11/15)
c)
{6x-3y=9
{x+5y=-9,5
{6x-3y=9
{x=-9,5-5y
69-9,5-5y)-3y=9
-57-30y-3y=9
-57-33y=9/+57
-33y=66//(-33)
y=-2
{y=-2
{x=-9,5-5*-2
{y=-2
{x=0,5